Building Confidence: Reducing Speaking Anxiety Among Blitar's EFL Students in the Post-Covid-19 era - sholikhi, fuad (Universitas Maritim Raja Ali Haji (UMRAH), 2025)
The COVID-19 pandemic necessitates a shift to online learning, which often results in more passive experiences for Students who majoring in sociology in Blitar. Despite the challenges of acquiring proficiency in a foreign language like English, many third-year students remain determined to improve their speaking skills and communication abilities to support their careers. The study aimed to understand the strategies students employed to overcome speaking anxiety in social interaction. Through semi-structured interviews and classroom observations, the research identified three primary approaches: collecting, grouping, and summarizing. The twelve Sociology students emphasized the importance of preparation in speaking, including studying and practicing pronunciation. A significant majority (84%) of students believed in the power of preparation, while 24% relied on relaxation techniques to manage anxiety. A smaller group (12%) exhibited minimal participation in speaking, reflecting a state of resignation. Engaging in small talk was identified as a potential strategy to address the challenges faced by students experiencing speaking anxiety in the classroom.